A Study of Splitskin Donor Area Healing - R. N. Sharma; M. T. Husain (Indian Journal of Plastic Surgery)
53 donor areas have been studied, and the role of depth of the wound, postoperative soakage, infection, immobilisation, instrument used for cutting the graft, and the closed, and exposure methods of management has been assessed, the results have been discussed and compared with available literature.